2017
DOI: 10.1186/s13058-017-0916-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of active tamoxifen metabolites predict long-term survival in adjuvantly treated breast cancer patients

Abstract: BackgroundControversies exist as to whether the genetic polymorphisms of the enzymes responsible for the metabolism of tamoxifen can predict breast cancer outcome in patients using adjuvant tamoxifen. Direct measurement of concentrations of active tamoxifen metabolites in serum may be a more biological plausible and robust approach. We have investigated the association between CYP2D6 genotypes, serum concentrations of active tamoxifen metabolites, and long-term outcome in tamoxifen treated breast cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(115 citation statements)
references
References 37 publications
(40 reference statements)
6
107
2
Order By: Relevance
“…However a recent prospective study did not observe any significant association between clinical benefit of TAM and plasma ENDO exposure in 247 patients with neo-adjuvant and metastatic breast cancer, 13 corroborated by another recent study in 667 patients. 14 On the contrary, Helland et al 28 reported a correlation between ENDO and 4-OHTAM concentrations and long-term survival in 99 retrospectively analyzed patients with adjuvant breast cancer. Therefore, the clinical utility of therapeutic drug monitoring of ENDO concentrations remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…However a recent prospective study did not observe any significant association between clinical benefit of TAM and plasma ENDO exposure in 247 patients with neo-adjuvant and metastatic breast cancer, 13 corroborated by another recent study in 667 patients. 14 On the contrary, Helland et al 28 reported a correlation between ENDO and 4-OHTAM concentrations and long-term survival in 99 retrospectively analyzed patients with adjuvant breast cancer. Therefore, the clinical utility of therapeutic drug monitoring of ENDO concentrations remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…This is a significant because women who are diagnosed with breast cancer use Tamoxifen for 5 or 10 years 41 . A recent study showed that lower active TAM metabolite concentrations in the serum was associated with poor outcome 42 . In combination with our data, showing TAM and 4-OH-Tam as potential substrates for bacterial GUS activity, this study suggests combined probiotic interventions might improve the outcome of breast cancer patients using tamoxifen by increasing serum active TAM metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…D. Johnson et al, 2004;Lien et al, 1988) Accordingly, poor metabolizers appear to have the lowest plasma endoxifen levels. (Helland et al, 2017;Madlensky et al, 2011) Extensive metabolizers have slightly higher Z-endoxifen concentrations than intermediate metabolizers. (Madlensky et al, 2011) Some research suggests that the total concentration of tamoxifen and its metabolites is sufficiently high so as to overwhelm and inhibit estrogen binding to the estrogen receptor, irrespective of an individual's CYP2D6 genotype and phenotype.…”
Section: Cyp2d6 and Tamoxifen Metabolismmentioning
confidence: 99%